Addition-curable liquid silicone composition
The addition-curing liquid silicone composition with yellow iron oxide and cerium oxide improves thermal conductivity and heat resistance, addressing the limitations of conventional compositions by providing durable and flexible silicone rubber for high-temperature applications in image forming apparatuses.
Patent Information
- Application Number
- JP2021170247
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-10-18
AI Technical Summary
Conventional silicone rubber compositions used in image forming apparatuses face challenges in achieving high thermal conductivity and heat resistance at temperatures above 200°C, particularly 300°C, due to the negative effects of high filler ratios, which lead to decreased heat resistance and mechanical properties.
An addition-curing liquid silicone composition containing a high proportion of thermally conductive inorganic fillers, including yellow iron oxide and cerium oxide or cerium hydroxide, along with specific organopolysiloxanes and organohydrogenpolysiloxanes, is formulated to enhance heat resistance and thermal conductivity.
The composition results in a highly thermally conductive silicone rubber with excellent heat resistance up to 350°C, maintaining flexibility and durability, suitable for use in fixing rolls and belts of image forming apparatuses.
Smart Images

Figure 0007611799000001 
Figure 0007611799000002 
Figure 0007611799000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an addition-curable liquid silicone composition. More specifically, the present invention relates to an addition-curable liquid silicone composition that provides a thermally conductive silicone rubber. In particular, the present invention relates to an addition-curable liquid silicone composition that provides a thermally conductive silicone rubber that is useful as a member for an image-forming device. [Background technology]
[0002] Silicone rubber has excellent electrical insulation, heat resistance, weather resistance, and flame retardancy, and is therefore used in a variety of fields, including electrical and electronic equipment, transport machinery parts, office automation equipment, and construction applications. In particular, its heat resistance has led to its use as a coating material for fixing members such as heater rolls, belts, and pressure rolls in image forming apparatus components such as copiers and laser beam printers. In particular, with the increasing speed and resolution of color copying, there is a demand for fixing rolls and fixing belts that have low hardness and high thermal conductivity, as well as improved heat resistance and toner release properties. For this reason, a configuration in which a highly thermally conductive silicone rubber layer is provided on a substrate and then coated with a fluororesin is often adopted.
[0003] Silicone rubber is generally made highly thermally conductive by adding a filler having high thermal conductivity to a silicone polymer. Specifically, silica, alumina, magnesium oxide, metal silicon, etc. are blended as thermally conductive fillers into silicone rubber that has been used in the past. However, a large amount of filler is required to obtain the required thermal conductivity. As a result, the filler ratio of the silicone composition increases, which increases the metallic impurities, hydroxyl groups, organic functional groups, etc. derived from the filler, resulting in problems such as a decrease in the heat resistance required for rubber rollers and belts.
[0004] As a method for improving the heat resistance of silicone rubber, it is known to blend additives such as cerium oxide, cerium hydroxide, iron oxide, and carbon black. As such silicone rubber, Patent Documents 1 to 3 describe a method of adding titanium oxide and iron oxide, a method of adding cerium oxide hydrate and / or zirconium oxide hydrate, and a method of adding yellow iron oxide in which aluminic acid or aluminate is dissolved. However, the fixing roll or belt may be subjected to a heat history of 250°C or more when the device is started up. In addition, when a fluororesin powder is thermally melted on the surface layer of the fixing roll or belt during production, it is necessary to bake under high temperature conditions of 320°C or more. Under these conditions, the effect of the conventional method is insufficient, and silicone rubber with improved heat resistance is desired. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2016-518461 [Patent Document 2] JP 2014-031408 A [Patent Document 3] Japanese Patent Application Publication No. 7-292256 Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, an object of the present invention is to provide an addition-curing liquid silicone composition, particularly a silicone composition for image-forming devices, which gives a silicone rubber that has excellent heat resistance at high temperatures of 200°C or higher, particularly 300°C or higher, and also has excellent thermal conductivity, and to provide a fixing roll and belt that use a cured product (i.e., silicone rubber) obtained by curing the composition. [Means for solving the problem]
[0007] As a result of intensive research conducted by the inventors in order to achieve the above-mentioned object, they discovered that the heat resistance of highly thermally conductive silicone rubber can be improved by adding yellow iron oxide and cerium oxide or cerium hydroxide to an addition-curable liquid silicone composition containing a high content of thermally conductive inorganic filler, which led to the completion of the present invention. That is, the present invention provides (A) an organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in each molecule and having an average degree of polymerization of less than 1,000: 100 parts by mass, (B) an organohydrogenpolysiloxane having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the ratio of the number of silicon-bonded hydrogen atoms in component (B) to the number of silicon-bonded alkenyl groups in component (A) is 0.3 to 3; (C) a thermally conductive inorganic filler having an average particle size of 1 to 50 μm: 40 to 800 parts by mass, (D) a hydrosilylation reaction catalyst: a catalytic amount, (E) yellow iron oxide: 0.1 to 10 parts by mass, and (F) At least one selected from cerium oxide and cerium hydroxide: 0.1 to 10 parts by mass The present invention provides an addition-curable silicone composition which is liquid at 25° C. and contains the following:
[0008] The present invention further provides the above-mentioned addition-curable liquid silicone composition for use in an image-forming apparatus, a cured product (i.e., silicone rubber) obtained by curing the composition, and a fixing roll and fixing belt using the cured product. Effect of the Invention
[0009] According to the present invention, it is possible to obtain a highly heat-conductive silicone rubber with excellent heat resistance. That is, the silicone rubber obtained by curing the addition-curing liquid silicone composition of the present invention exhibits excellent heat resistance at 230°C or higher, particularly at 350°C, and provides a fixing roll and fixing belt with excellent durability under heat, flexibility and retention over time. Therefore, the obtained silicone rubber can be suitably used as a member for an image-forming device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The composition of the present invention will be described in detail below. [Component (A)] Component (A) is an organopolysiloxane that is liquid at 25°C and has two or more alkenyl groups bonded to silicon atoms in each molecule and an average degree of polymerization of less than 1,000. It is the base polymer (main component) of the composition of the present invention.
[0011] The molecular structure of component (A) may be any structure that satisfies the above requirements, and may be, for example, linear or branched. A linear diorganopolysiloxane whose main chain is essentially composed of repeating diorganosiloxane units and whose molecular chain ends are blocked with triorganosiloxy groups is preferred. In addition, the position of the silicon atom to which the alkenyl group is bonded in the molecule of the organopolysiloxane may be either one or both of the molecular chain ends and / or the middle of the molecular chain. Particularly preferred as component (A) is a linear diorganopolysiloxane containing alkenyl groups bonded to silicon atoms at least at both molecular chain ends.
[0012] The alkenyl group bonded to the silicon atom preferably has 2 to 8 carbon atoms, and more preferably has 2 to 4 carbon atoms. Examples include a vinyl group, an allyl group, a propenyl group, a butenyl group, a pentenyl group, a hexenyl group, a cyclohexenyl group, and a heptenyl group, and the vinyl group is particularly preferred.
[0013] Component (A) is characterized by having two or more alkenyl groups bonded to silicon atoms, preferably 2 to 50, and particularly preferably 2 to 20. Furthermore, the content of alkenyl groups is preferably 0.001 to 10 mol %, and particularly preferably 0.01 to 5 mol %, of the total number of monovalent organic groups bonded to silicon atoms.
[0014] Component (A) has, as a monovalent organic group other than an alkenyl group bonded to a silicon atom, a monovalent hydrocarbon group preferably having 1 to 12 carbon atoms, more preferably 1 to 10 carbon atoms. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, cyclohexyl, and heptyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl and phenethyl; and halogen-substituted alkyl groups such as chloromethyl, 3-chloropropyl, and 3,3,3-trifluoropropyl. Methyl groups are particularly preferred.
[0015] The (A) component is characterized by having an average degree of polymerization of less than 1000. The average degree of polymerization is preferably 50 or more and less than 1,000, and more preferably 100 or more and 800 or less. If the degree of polymerization is less than the lower limit, the mechanical properties of the resulting silicone rubber may be insufficient. If the average degree of polymerization is 1,000 or more, the viscosity of the resulting silicone composition may be too high, which may result in poor filling properties of the thermally conductive inorganic filler. When the (A) component is a mixture of multiple components, the degree of polymerization of the (A) component is the sum of the products of the degrees of polymerization and the mass fractions of the respective components. In this specification, the "degree of polymerization" refers to an average degree of polymerization, which can be determined from the weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions using polystyrene as a standard substance (the same applies hereinafter). [Measurement conditions] Developing solvent: toluene Flow rate: 1mL / min Detector: Refractive index detector (RI) Column: KF-805L x 2 (Shodex) Column temperature: 25℃ Sample injection volume: 20 μL (toluene solution with a concentration of 0.1% by mass)
[0016] Examples of the component (A) include dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, methylvinylpolysiloxanes capped at both molecular chain terminals with trimethylsiloxy groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, dimethylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, methylvinylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, and mixtures of two or more of these organopolysiloxanes.
[0017] The organopolysiloxane may be used alone or in combination of two or more. Particularly preferred is a combination of a linear organopolysiloxane having alkenyl groups at both ends and a linear organopolysiloxane having two or more alkenyl groups on the side chain. The ratio of the two is not particularly limited. The mass ratio of the linear organopolysiloxane having alkenyl groups at both ends and the linear organopolysiloxane having two or more alkenyl groups on the side chain may be 1:99 to 99:1, preferably 20:80 to 80:20, and more preferably 30:70 to 70:30.
[0018] [(B) Component] The (B) component is an organohydrogenpolysiloxane that mainly undergoes a hydrosilylation addition reaction with the alkenyl groups in the (A) component and acts as a crosslinking agent (curing agent). The molecular structure of the (B) component can be, for example, a linear, cyclic, branched, or three-dimensional network (resinous) structure. The (B) component must have at least two, preferably three or more, hydrogen atoms bonded to silicon atoms (hydrosilyl groups) in one molecule, and it is desirable to have usually 2 to 300, preferably 3 to 200, and more preferably 4 to 100 hydrosilyl groups. Such hydrosilyl groups may be located at either the molecular chain terminal or the middle of the molecular chain, or may be located at both of these. The (B) component is preferably liquid at 25°C. Most preferably, the (B) component is a linear organohydrogenpolysiloxane that has hydrosilyl groups at both terminals and in the side chain and is liquid at 25°C.
[0019] The organohydrogenpolysiloxane can be represented, for example, by the following average composition formula (1). [ka]
[0020] In formula (1), R 1 are each independently a monovalent hydrocarbon group having no aliphatic unsaturated bond, such as an alkenyl group, and preferably having 1 to 10 carbon atoms. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl; and groups in which some or all of the hydrogen atoms of these groups have been substituted with halogen atoms such as fluorine, bromine, and chlorine, such as a chloromethyl group, a chloropropyl group, a bromoethyl group, and a trifluoropropyl group. 1is preferably an alkyl group or an aryl group, and more preferably a methyl group. In addition, a is preferably a positive number of 0.7 to 2.1, b is preferably a positive number of 0.001 to 1.0, and a+b is preferably a positive number of 0.8 to 3.0, and more preferably a is a positive number of 1.0 to 2.0, b is preferably a positive number of 0.01 to 1.0, and a+b is preferably a positive number of 1.5 to 2.5.
[0021] Examples of the organohydrogenpolysiloxane include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(hydrogendimethylsiloxy)methylsilane, tris(hydrogendimethylsiloxy)phenylsilane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymer, methylhydrogenpolysiloxane capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane copolymer capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymer capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane-diphenylsiloxane copolymer capped with trimethylsiloxy groups at both molecular chain ends, and dimethylsiloxane copolymers, methylhydrogenpolysiloxanes capped at both molecular ends with dimethylhydrogensiloxy groups, dimethylpolysiloxanes capped at both molecular ends with dimethylhydrogensiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymers capped at both molecular ends with dimethylhydrogensiloxy groups, dimethylsiloxane-methylphenylsiloxane copolymers capped at both molecular ends with dimethylhydrogensiloxy groups, dimethylsiloxane-diphenylsiloxane copolymers capped at both molecular ends with dimethylhydrogensiloxy groups, methylphenylpolysiloxanes capped at both molecular ends with dimethylhydrogensiloxy groups, diphenylpolysiloxanes capped at both molecular ends with dimethylhydrogensiloxy groups, and compounds in which some or all of the methyl groups in each of these exemplary compounds have been replaced with other alkyl groups such as ethyl groups or propyl groups, compounds of the formula: R 2 3 SiO 1 / 2 Siloxane units represented by the formula: R2 2 HSiO 1 / 2 Siloxane units represented by the formula: SiO 4 / 2 Organosiloxane copolymers consisting of siloxane units represented by the formula: R 2 2 HSiO 1 / 2 Siloxane units represented by the formula: SiO 4 / 2 Organosiloxane copolymers consisting of siloxane units represented by the formula: R 2 HSiO 2 / 2 Siloxane units represented by the formula: R 2 SiO 3 / 2 Siloxane units or formula: HSiO 3 / 2 and mixtures of two or more of these organopolysiloxanes. 2 is a monovalent hydrocarbon group other than an alkenyl group.
[0022] The amount of the (B) component is such that the number of hydrosilyl groups contained in the composition is 0.3 to 3 per total number of silicon-bonded alkenyl groups contained in the composition. In particular, the ratio of the number of hydrosilyl groups contained in the (B) component to the number of silicon-bonded alkenyl groups contained in the (A) component is 0.3 to 3, preferably 0.4 to 2, and more preferably 0.4 to 1.6. If the number of the hydrosilyl groups is less than the lower limit, the composition will not cure sufficiently. If the number of the hydrosilyl groups exceeds the upper limit, the hardness of the obtained silicone rubber cured product may be extremely hard or the heat resistance may be extremely poor. The amount is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 15 parts by mass, per 100 parts by mass of the (A) component.
[0023] The organohydrogenpolysiloxanes may be used alone or in combination of two or more.
[0024] [(C) component] Component (C) is a thermally conductive inorganic filler having an average particle size of 1 to 50 μm. Component (C) acts to impart thermal conductivity to the resulting silicone rubber. In order to improve the heat resistance of the silicone rubber, it is preferable that the thermal conductivity of the thermally conductive inorganic filler is 5 W / m·K or more. If the thermally conductive inorganic filler has a thermal conductivity of 5 W / m·K or more, a composition containing a large amount of the thermally conductive filler can impart an excellent effect of improving heat resistance to the silicone rubber.
[0025] In the silicone composition of the present invention, the amount of the thermally conductive filler is 40 to 800 parts by mass, preferably 100 to 500 parts by mass, and more preferably 180 to 480 parts by mass, per 100 parts by mass of the component (A). If it is less than the lower limit, the thermal conductivity of the cured product of the silicone composition will be insufficient, which is not preferred. If it is more than the upper limit, the viscosity of the composition will be too high, which may result in poor handling. If it is within the above range, the thermal conductivity of the cured product will be 0.4 W / m·K or more, which is preferred.
[0026] The thermally conductive inorganic filler is characterized by having an average particle size of 1 to 50 μm, preferably 2 to 20 μm. If the average particle size is smaller than the lower limit, the hardness of the silicone rubber may increase significantly, or the electrical resistance may change over time. If the average particle size is larger than the upper limit, it may cause unevenness on the rubber surface. In the present invention, the average particle size refers to the d50 particle size measured as a weight average value (i.e., median size) using a particle size distribution measuring device using a laser light diffraction method or the like (hereinafter the same).
[0027] Examples of the thermally conductive inorganic filler include quartz powder, metal oxides such as alumina and zinc oxide, metal particles such as silver, copper and metallic silicon, and composite metals such as boron nitride, aluminum nitride, silicon nitride and silicon carbide, and in the present invention, it is particularly preferable to use crystalline silica, alumina, metallic silicon and zinc oxide. The thermally conductive inorganic fillers may be used alone or in combination of two or more.
[0028] The thermally conductive inorganic filler may be surface-treated with a silane coupling agent or a partial hydrolyzate thereof, an alkylalkoxysilane or a partial hydrolyzate thereof, an organic silazanes, an organopolysiloxane oil, an organopolysiloxane containing a hydrolyzable functional group, or the like. The method of surface treatment is not particularly limited. The thermally conductive inorganic filler may be surface-treated in advance before being mixed with other components. Alternatively, the surface treatment may be performed when the filler is mixed with the organopolysiloxane of component (A).
[0029] The thermally conductive inorganic filler may be mixed with component (A) at room temperature using equipment such as a planetary mixer or kneader, or may be mixed at an elevated temperature of 100 to 200°C.
[0030] In addition to the above-mentioned thermally conductive inorganic fillers, the silicone composition of the present invention may further contain reinforcing silica such as fumed silica or precipitated silica for the purposes of improving rubber strength and preventing the settling of the thermally conductive inorganic fillers, provided that the thermal conductivity properties are not impaired. 2 / g~300m 2 / g range is desirable. Examples of the reinforcing silica include fumed silica (fumed silica, dry silica) and precipitated silica (precipitated silica, wet silica). Among them, fumed silica (dry silica) whose surface is hydrophobized with organopolysiloxane, organopolysilazane, chlorosilane, alkoxysilane, or the like is more preferable. These silicas may be used alone or in combination of two or more.
[0031] The content of the reinforcing silica in the silicone composition of the present invention is 0 to 20 parts by mass per 100 parts by mass of component (A), and, when blended, is preferably 0.5 to 10 parts by mass. If the reinforcing silica is contained in an amount greater than the upper limit, the hardness of the obtained silicone rubber may increase, and the blendability of the thermally conductive inorganic filler may deteriorate.
[0032] [(D) Hydrosilylation reaction catalyst] Component (D) is a hydrosilylation catalyst, which promotes the addition reaction between the silicon-bonded alkenyl group contained in the composition and the hydrosilyl group contained in the composition. It mainly promotes the addition reaction between the silicon-bonded alkenyl group in component (A) and the hydrosilyl group in component (B). This hydrosilylation catalyst is not particularly limited, and examples thereof include platinum group metals such as platinum, palladium, and rhodium; chloroplatinic acid; alcohol-modified chloroplatinic acid; coordination compounds of chloroplatinic acid with olefins, vinylsiloxanes, or acetylene compounds; platinum group metal compounds such as tetrakis(triphenylphosphine)palladium and chlorotris(triphenylphosphine)rhodium, and the like, and preferably platinum group metal compounds.
[0033] The amount of the (D) component to be blended may be an effective amount as a catalyst (catalytic amount). For example, the amount is preferably 1 to 500 ppm, more preferably 5 to 100 ppm, calculated as the mass of the catalytic metal element relative to the total mass of the (A) component. If the amount is less than the lower limit, the addition reaction may be significantly slowed down, and the composition may not be cured. If the amount exceeds the upper limit, the heat resistance of the cured product may be reduced.
[0034] The hydrosilylation reaction catalyst of the component (D) may use either a single compound, or a combination of two or more different compounds.
[0035] [(E) Yellow iron oxide] Component (E) is yellow iron oxide, which, when used together with component (F), described below, inhibits the increase in hardness of silicone rubber when heated and maintains the flexibility of the rubber.
[0036] Yellow iron oxide has the chemical formula Fe 2 O 3 H 2Examples of such compounds include iron oxide (III) monohydrate represented by O and α-iron oxyhydroxide represented by α-FeOOH. The appearance is yellow to yellowish brown, and the shape is generally needle-like to spindle-like particles. Synthetic products can be obtained by crushing natural minerals such as goethite, or by adding a base to a solution containing trivalent iron ions to precipitate them. Commercially available products include the Todacolor TSY series (manufactured by Toda Kogyo Co., Ltd.) and the TAROX-LL series (manufactured by Titanium Kogyo Co., Ltd.). The particle size is not particularly limited, but it is preferable to use one with few aggregates and a 45 μm sieve residue of 0.01% or less.
[0037] The amount of yellow iron oxide added is 0.1 to 10 parts by mass, and preferably 0.2 to 6 parts by mass, per 100 parts by mass of component (A). If the amount added is less than the lower limit, the heat resistance of the silicone rubber will not improve, whereas if the amount added exceeds the upper limit, the mechanical properties of the silicone rubber may decrease significantly.
[0038] [(F) Cerium compounds] Component (F) is one or more cerium compounds selected from cerium oxide and cerium hydroxide. Component (F) significantly improves the heat resistance of silicone rubber when used in combination with component (E). Cerium oxide and cerium hydroxide may be commercially available products. Commercially available cerium oxide products include Showlox FL-2 (manufactured by Showa Denko K.K.), SN-2 (manufactured by Nikki Co., Ltd.), and Cerium Oxide S (manufactured by Anan Kasei Co., Ltd.). Commercially available cerium hydroxide products include cerium hydroxide (manufactured by Nikki Co., Ltd.) and Cerhydrate 90 (manufactured by Tribach Industry AG).
[0039] The amount of component (F) added is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 6 parts by mass, per 100 parts by mass of component (A). If the amount is less than the lower limit, the heat resistance of the silicone rubber will not improve. If the amount is more than the upper limit, the mechanical properties of the silicone rubber may be significantly reduced.
[0040] The component (F) may be either cerium oxide or cerium hydroxide, or a combination of cerium oxide and cerium hydroxide. When cerium oxide and cerium hydroxide are used in combination, the total amount thereof should be within the above range.
[0041] The blending ratio of the above (E) yellow iron oxide and (F) cerium compound is preferably 10:90 to 95:5, more preferably 50:50 to 80:20, in terms of mass ratio.
[0042] [Other ingredients] In addition to the above components (A) to (F), the silicone composition of the present invention may contain other optional components, such as a reaction inhibitor.
[0043] Reaction control agent The reaction inhibitor is not particularly limited as long as it is a compound that has a curing inhibitory effect on the above (D) hydrosilylation reaction catalyst, and known compounds can be used. For example, phosphorus-containing compounds such as triphenylphosphine; nitrogen-containing compounds such as tributylamine, tetramethylethylenediamine, and benzotriazole; sulfur-containing compounds; acetylene-based compounds such as acetylene alcohols; compounds containing two or more alkenyl groups; hydroperoxy compounds; maleic acid derivatives, etc. can be mentioned. The degree of the curing inhibitory effect varies depending on the chemical structure of the reaction inhibitor. Therefore, it is preferable to adjust the amount of reaction inhibitor to an optimal amount for each reaction inhibitor used. By adding an optimal amount of reaction inhibitor, the composition has excellent long-term storage stability and curing properties at room temperature.
[0044] Other additives The silicone composition of the present invention may contain other fillers than the component (C) as long as the effect of the present invention is not impaired. The other fillers may be known fillers used in silicone compositions. For example, organic resin hollow fillers for density adjustment, polymethylsilsesquioxane fine particles (so-called silicone resin powder) and spherical rubber powder for improving surface slipperiness, fumed titanium dioxide, magnesium oxide, and iron (II) oxide for flame retardants and colorants, diatomaceous earth, talc, kaolinite, glass fiber, aluminum hydroxide, magnesium carbonate, calcium carbonate, and zinc carbonate for extenders, carbon black for imparting electrical conductivity, and carbon fiber powder and graphite having a fiber length of 20 to 500 μm for imparting thermal conductivity and electrical conductivity, etc. may also be mentioned. In addition, fillers obtained by subjecting the surface of these fillers to hydrophobic treatment with organosilicon compounds such as organoalkoxysilane compounds, organochlorosilane compounds, organosilazane compounds, and low-molecular-weight siloxane compounds may also be mentioned.
[0045] Examples of other additives that may be blended include organopolysiloxanes that contain one silicon-bonded hydrogen atom per molecule and no other functional groups, organopolysiloxanes that contain one silicon-bonded alkenyl group per molecule and no other functional groups, non-functional organopolysiloxanes that contain no silicon-bonded hydrogen atoms, silicon-bonded alkenyl groups, or other functional groups (so-called dimethyl silicone oil), organic solvents, creep hardening inhibitors, plasticizers, thixotropy-imparting agents, pigments, dyes, and fungicides.
[0046] The above-mentioned other components may be used alone or in combination of two or more. The blending amount is not particularly limited, and may be appropriately adjusted within a range that does not impair the effects of the present invention. For example, when a conductivity imparting agent such as carbon black is blended, the amount may be 3 to 20 parts by mass per 100 parts by mass of the (A) component.
[0047] <Preparation of Addition-Curable Liquid Silicone Composition> The addition curing liquid silicone composition can be prepared by uniformly mixing the above components (A) to (F) and other components as necessary. The components can be mixed using a known method and device for producing a liquid silicone composition. Examples of the device include known kneading devices such as two-roll, three-roll, kneader mixer, planetary mixer, Ross mixer, and acoustic vibration mixer. The components (A) to (F) may all be mixed together at room temperature. Alternatively, when performing heat treatment, for example, a mixture of the components (A) and (C) and optionally other fillers such as a fine powder silica-based filler is heat-treated and mixed at 100 to 200°C for 10 minutes to 3 hours to prepare a heat-treated compound, and then the components (B), (D), (E), and (F) as well as the other additives described above are mixed in a kneader to prepare the heat-treated compound. Furthermore, for the purpose of improving dispersibility in the silicone composition, components (E) and (F) may be mixed in advance with a small amount of component (A) and dispersed using a paint mill, centrifugal stirrer mixer, ultrasonic disperser, or the like to prepare a paste, which can then be added to the mixture of components (A) to (D).
[0048] The silicone composition of the present invention may be a two-liquid mixed silicone composition for cast molding or injection molding. That is, (D) a hydrosilylation reaction catalyst is added to one of the components (A) and (C) in advance, with respect to half of the mixture, and mixed. (B) an organohydrogenpolysiloxane and a reaction inhibitor are added to the other mixture and mixed. The silicone composition can be easily prepared by mixing both components just before use. In this case, the other components (E) and (F) may be added to either one side or both sides.
[0049] The silicone composition of the present invention is a liquid composition at 25° C. The silicone composition of the present invention preferably has a viscosity at 25° C. of 1 to 2,000 Pa·s, more preferably 5 to 1,000 Pa·s, as measured by a method using a B-type rotational viscometer as described in JIS K 7117-1:1999. If the viscosity is within this range, when the composition is cast into a fixing roll for an image forming apparatus or applied as a thin film to the shape of a fixing belt, casting abnormalities, coating unevenness, and insufficient adhesive strength to a core metal or belt base after curing are unlikely to occur, and the composition can be suitably used.
[0050] The silicone composition of the present invention can be molded into the required application by various molding methods that are usually used to mold silicone, such as cast molding, LIM injection machine, and mold pressure molding. The molding conditions are not particularly limited, but it is preferable to cure with a heat history in the range of several seconds to 1 hour at 100 to 400°C. In addition, in the case of secondary vulcanization after molding, it is preferable to perform secondary vulcanization in the range of 1 to 30 hours at 150 to 250°C. The cured product (i.e., silicone rubber) obtained by curing the silicone composition of the present invention can have high thermal conductivity and heat resistance.
[0051] The cured layer (silicone rubber layer) obtained from the silicone composition of the present invention has high thermal conductivity. Silicone rubber used for fixing rolls and belts preferably has a thermal conductivity of 0.4 W / mK or more, and more preferably 0.5 to 3.0 W / mK.
[0052] The present invention further provides a fixing roll or fixing belt having the above-mentioned cured product (i.e., silicone rubber). The fixing roll has the above-mentioned cured product layer (silicone rubber layer) formed on a core metal. The material, dimensions, etc. of the core metal may be appropriately selected according to the type of roll. For example, aluminum, iron, stainless steel (SUS), polyether ether ketone (PEEK) of heat-resistant thermoplastic resins, etc. are used as the core metal. It is preferable that the surface of these core metals is subjected to a primer treatment with a silane coupling agent, a silicone adhesive, etc., in order to further strengthen the adhesion with the silicone rubber layer. The molding and curing method of the silicone composition may be appropriately selected. For example, it can be molded by a method such as casting, transfer molding, injection molding, ring coating molding, knife coating, etc., and cured by heating. The silicone rubber layer may be a layer made of one layer of silicone rubber, or a multi-layer made of two or more layers of silicone rubber having different types and amounts of (C) thermally conductive inorganic filler. In the fixing roll, the total thickness of the silicone rubber layer is preferably 50 μm to 20 mm, particularly 0.2 mm to 6 mm. If it is too thin, sufficient rubber elasticity may not be obtained. If it is too thick, the heat transfer characteristics between the core metal and the rubber roll surface may be impaired.
[0053] The fixing roll may further have a fluororesin layer or a fluororubber layer on the outer surface of the silicone rubber layer for the purpose of releasing the molten toner. The fluororesin layer is formed of a fluororesin coating material or a fluororesin tube, and covers the silicone rubber layer. Here, examples of the fluororesin coating material include polytetrafluoroethylene resin (PTFE) latex and powder baked and melted and coated at 300°C or higher. Examples include Daiel latex (manufactured by Daikin Industries, fluoro latex). The fluororubber layer can be obtained by applying an uncrosslinked fluororubber composition to the outer surface of the silicone rubber layer and adhering it to the silicone rubber layer by crosslinking reaction or the like. In addition, by covering the outside of the silicone composition with a fluororesin tube, the fluororesin can be adhered to the surface layer of the silicone rubber at the same time as the silicone composition is cured. Alternatively, the fixing roll can be obtained by molding the silicone composition into a roll shape on the surface of a core metal and curing it, and then adhering the fluororesin tube to the surface layer of the silicone rubber using an adhesive or a primer.
[0054] As the fluorine-based resin, commercially available products can be used, such as polytetrafluoroethylene resin (PTFE), tetrafluoroethylene-perfluoroalkylvinyl ether copolymer resin (PFA), fluorinated ethylene-polypropylene copolymer resin (FEP), polyvinylidene fluoride resin (PVDF), polyvinyl fluoride resin, etc. In particular, a PFA tube is preferable.
[0055] The thickness of the fluororesin or fluororubber layer formed on the outer surface of the silicone rubber layer is preferably 1 μm to 500 μm, particularly 10 μm to 100 μm. If it is too thin, it may break, wrinkle, or peel when an external stress is applied to the roll, while if it is too thick, it may impair the rubber elasticity of the roll surface or cause defects in appearance such as cracks and breaks.
[0056] The present invention further provides a fixing belt having the silicone rubber layer. The fixing belt is obtained by laminating the silicone rubber layer on a belt substrate. The belt substrate can be made of a known material, such as a metal belt made of nickel electroforming, SUS, aluminum, or the like, or an organic resin film made of polyimide resin, polyamide resin, polyamideimide resin, or the like. The shape, dimensions, etc., of the belt substrate can be appropriately selected according to the type of belt.
[0057] The molding and curing methods of the silicone composition are as described above. The silicone rubber layer formed on the fixing belt substrate may be a single layer, or may be a multi-layer consisting of two or more layers of silicone rubber with different amounts of the thermally conductive inorganic filler (C) component. The total thickness of the silicone rubber layer is preferably 30 μm to 5 mm, and more preferably 50 μm to 800 μm. If it is too thin, rubber elasticity may not be obtained, and if it is too thick, the heat transfer characteristics between the belt surface and the substrate may be impaired.
[0058] It is desirable to laminate a fluororesin or fluororubber layer on the silicone rubber layer for the purpose of releasing the molten toner. The types of fluororesin and fluororubber are the same as those described for the fixing roll. In the case of a fixing belt, a fluororesin layer is preferable in order to minimize the loss of thermal conductivity of the rubber cured layer, and more preferably, a belt made of polytetrafluoroethylene resin (PTFE) latex or powder sintered and melted, or a PFA tube is disposed on the outer periphery. The thickness of the fluororesin layer is preferably 1 μm to 100 μm, particularly 2 μm to 70 μm. If it is too thin, the belt may break, wrinkle, or peel when an external stress is applied to the belt. If it is too thick, the thermal conductivity on the vertical side of the belt axis may decrease, resulting in a decrease in toner melting performance, loss of rubber elasticity on the surface, or poor appearance such as cracks or breakage. EXAMPLES
[0059] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0060] The evaluation tests carried out in the following Examples and Comparative Examples are as follows. The average particle size described in the Examples and Comparative Examples refers to the d50 particle size measured as a weight average value using a particle size distribution measuring device by a laser light diffraction method or the like.
[0061] Thermal Conductivity Measurement: The thermal conductivity (W / m K) of a 12 mm thick sheet was measured using a rapid thermal conductivity meter (QTM-700, Kyoto Electronics Co., Ltd.).
[0062] Volume resistivity measurement: The volume resistivity (insulation) (Ω·m) of silicone rubber was measured based on the double ring electrode method of JIS K6271:2008. The volume resistivity measurement conditions were sample size 1mm thickness x 100mm width x 100mm length, and voltage 500V. The volume resistivity (conductivity) (Ω·m) of silicone rubber was measured based on the parallel terminal electrode method of JIS K6271: 2008. The volume resistivity measurement conditions were: sample size 1mm thick x 20mm wide x 150mm long, distance between current electrodes 100mm, distance between potential difference electrodes 50mm, and current supply 1mA.
[0063] Rubber properties measurement: Using a 2 mm thick test sheet, the hardness (Durometer A), tensile strength (MPa), and elongation at break (%) were measured in accordance with JIS K 6249:2003. Next, the 2 mm thick test sheet was placed in a 230°C dryer for 21 days and in a 350°C dryer for 2 hours, and then the hardness (Durometer A), tensile strength (MPa), and elongation at break (%) were measured using the same methods as above.
[0064] Bend test: A 1 mm thick sheet was cut into a shape of 20 mm x 100 mm and bent at an angle of 180 degrees with a radius of curvature of 1 mm. Sheets that showed cracks or fissures were rated as ×, and those that showed no change in appearance were rated as ○. Next, the 1 mm thick test sheet was placed under two conditions, 21 days in a 230° C. dryer and 2 hours in a 350° C. dryer, and then subjected to a bending test in the same manner as above.
[0065] The organopolysiloxanes, organohydrogenpolysiloxanes, and fumed silicas used in the following Examples and Comparative Examples are as follows. Organopolysiloxane A1: A linear dimethylpolysiloxane that is liquid at 25°C and has both ends capped with dimethylvinylsiloxy groups, a degree of polymerization of 200, and a vinyl value of 0.00013 mol / g. Organopolysiloxane A2: A linear dimethylpolysiloxane that is liquid at 25°C, has a degree of polymerization of 700, and a vinyl value of 0.000075 mol / g, and is end-blocked at both ends with trimethylsiloxy groups and has vinyl groups on the side chains. Organohydrogenpolysiloxane B: A linear methylhydrogenpolysiloxane that has hydrosilyl groups at both ends and on the side chains and is liquid at 25°C, with a degree of polymerization of 17 and a hydrosilyl amount of 0.0038 mol / g. Fumed silica: specific surface area is 110m 2 / g of hydrophobically treated fumed silica, R-972 (manufactured by Nippon Aerosil Co., Ltd.)
[0066] [Example 1] 40 parts by mass of organopolysiloxane A1, 60 parts by mass of organopolysiloxane A2, 1 part of fumed silica R-972, and 200 parts by mass of M-Si#600 (Kinsei Matec Co., Ltd., thermal conductivity of filler: 160 W / m K), a crushed metal silicon powder with an average particle size of 6 μm, were placed in a planetary mixer and stirred for 2 hours at room temperature (23°C). The above materials were then heat-treated in the planetary mixer at 150°C for 2 hours, and then cooled to room temperature to obtain thermally conductive base 1. Next, the thermal conductive base 1 obtained above was treated with Todacolor TSY-1 (Fe 2 O 3 H 2O 86% or more, yellow iron oxide, 1.0 part by mass, manufactured by Toda Kogyo Co., Ltd., and 0.5 part by mass of SN-2 (manufactured by Nikki Co., Ltd.), which is cerium oxide, were added, and the mixture was stirred for another hour with a planetary mixer. To the resulting mixture, 2.2 parts by mass of organohydrogenpolysiloxane B, 0.05 parts by mass of ethynylcyclohexanol as a reaction inhibitor, and 0.1 parts by mass of platinum catalyst (Pt concentration 1% by mass) were added. Stirring was continued for 15 minutes, and a liquid product was obtained at 25°C. The product was designated as silicone composition (Example-1). The viscosity at 25° C. of the silicone composition (Example 1) obtained above was measured using a B-type rotational viscometer as described in JIS K7117-1:1999.
[0067] The above silicone composition (Example 1) was press-cured for 10 minutes at 120°C, and then post-cured for 4 hours in an oven at 200°C to produce silicone rubbers (test sheets) having a thickness of 1 mm, 2 mm, or 12 mm. The thermal conductivity, volume resistivity, rubber properties, and heat resistance of each test sheet were evaluated according to the evaluation methods described above. The results are shown in Table 1.
[0068] [Example 2] The steps of Example 1 were repeated, except that cerium oxide was replaced with cerium hydroxide, Cerhydrate 90 (manufactured by Treibach Industry AG), to obtain a silicone composition (Example 2) that was liquid at 25° C. The viscosity of the silicone composition at 25° C. was measured using a B-type rotational viscometer as described in JIS K7117-1:1999. The silicone composition was cured in the same manner as in Example 1 to obtain silicone rubber (test sheets) having a thickness of 1 mm, 2 mm, or 12 mm. The obtained silicone rubber was evaluated for thermal conductivity, volume resistivity, rubber properties, and heat resistance according to the evaluation methods described above. The results are shown in Table 1.
[0069] [Example 3] 40 parts by mass of organopolysiloxane A1, 60 parts by mass of organopolysiloxane A2, 1 part by mass of fumed silica R-972, and 250 parts by mass of Crystallite VXS-2 (manufactured by Tatsumori Co., Ltd., thermal conductivity of filler: 7 W / m K), which is a crushed crystalline silica powder with an average particle size of 5 μm, were placed in a planetary mixer and stirred at room temperature for 2 hours to obtain thermally conductive base 2. Next, 0.3 parts by mass of TAROX-LL-XLO (α-FeOOH 87.5% or more, yellow iron oxide, manufactured by Titan Kogyo Co., Ltd.) and 0.2 parts by mass of cerium oxide SN-2 were added to the thermally conductive base 2 obtained above, and the mixture was further stirred for 1 hour with a planetary mixer. 2.2 parts by mass of organohydrogenpolysiloxane B, 0.05 parts by mass of ethynylcyclohexanol as a reaction inhibitor, and 0.1 parts by mass of platinum catalyst (Pt concentration 1% by mass) were added to the obtained mixture. Stirring was continued for 15 minutes to obtain a liquid product at 25°C. The product was designated as silicone composition (Example-3). The viscosity of the silicone composition at 25°C was measured using a B-type rotational viscometer described in JIS K7117-1:1999. The silicone composition (Example 3) was cured in the same manner as in Example 1 to obtain silicone rubber (test sheets) having a thickness of 1 mm, 2 mm, or 12 mm. The obtained silicone rubber was evaluated for thermal conductivity, volume resistivity, rubber properties, and heat resistance according to the evaluation methods described above. The results are shown in Table 1.
[0070] [Example 4] 40 parts by mass of organopolysiloxane A1, 60 parts by mass of organopolysiloxane A2, 1 part of fumed silica R-972, and 450 parts by mass of spherical alumina powder AS-40 (manufactured by Showa Denko K.K., thermal conductivity of filler: 21 W / m K) with an average particle size of 12 μm were placed in a planetary mixer and stirred for 2 hours at room temperature (23°C). The above materials were then heated to 150°C in the planetary mixer and heat-treated for 2 hours, after which they were cooled to room temperature to obtain thermally conductive base 4. Next, Todacolor TSY-1 (Fe 2 O 3 ;·H 26.0 parts by mass of yellow iron oxide (O 86% or more, manufactured by Toda Kogyo Co., Ltd.) and 0.5 parts by mass of cerium oxide SN-2 were added, and the mixture was further stirred for 1 hour with a planetary mixer. 2.2 parts by mass of organohydrogenpolysiloxane B, 0.05 parts by mass of ethynylcyclohexanol as a reaction inhibitor, and 0.1 parts by mass of platinum catalyst (Pt concentration 1% by mass) were added to the resulting mixture, and stirring was continued for 15 minutes to obtain a liquid product at 25°C. This product was designated as silicone composition (Example-4). The viscosity of the silicone composition at 25°C was measured with a B-type rotational viscometer described in JIS K7117-1:1999. The silicone composition (Example 4) was cured in the same manner as in Example 1 to obtain silicone rubber (test sheets) having a thickness of 1 mm, 2 mm, or 12 mm. The obtained silicone rubber was evaluated for thermal conductivity, volume resistivity, rubber properties, and heat resistance according to the evaluation methods described above. The results are shown in Table 1.
[0071] [Example 5] 40 parts by mass of organopolysiloxane A1, 60 parts by mass of organopolysiloxane A2, 300 parts by mass of calcined zinc oxide powder (manufactured by Hakusui Tech Co., Ltd., thermal conductivity of filler: 54 W / m K) which is zinc oxide powder with an average particle size of 10 μm, and 5 parts by mass of Denka Black powder (manufactured by Denka Co., Ltd.) which is conductive carbon powder were placed in a planetary mixer and stirred at room temperature (23°C) for 2 hours. The above materials were then heated to 150°C in the planetary mixer and heat-treated for 2 hours, after which they were cooled to room temperature to obtain thermally conductive base 5. Next, 1.0 part by mass of TAROX-LL-XLO (α-FeOOH 87.5% or more, yellow iron oxide, manufactured by Titan Kogyo Co., Ltd.) and 6.0 parts by mass of Cerhydrate 90 of cerium hydroxide were added to the thermally conductive base 5 obtained above, and the mixture was further stirred for 1 hour with a planetary mixer. 2.2 parts by mass of organohydrogenpolysiloxane B, 0.05 parts of ethynylcyclohexanol as a reaction inhibitor, and 0.3 parts by mass of platinum catalyst (Pt concentration 1% by mass) were added to the obtained mixture. Stirring was continued for 15 minutes to obtain a liquid product at 25°C. The product was designated as silicone composition (Example-5). The viscosity of the silicone composition at 25°C was measured using a B-type rotational viscometer described in JIS K7117-1:1999. The silicone composition (Ex.-5) was cured in the same manner as in Example 1 to obtain silicone rubber (test sheets) having a thickness of 1 mm, 2 mm, or 12 mm. The obtained silicone rubber was evaluated for thermal conductivity, volume resistivity, rubber properties, and heat resistance according to the evaluation methods described above. The results are shown in Table 1. The silicone rubber obtained in Example 5 is conductive and has a volume resistivity of 11 Ω·m, as shown in Table 1 below.
[0072] [Comparative Example 1] Instead of the iron(III) oxide monohydrate used in Example 1, hydrate-free iron(III) oxide, Bayferrox 110M (Fe 2 O 3 Example 1 was repeated, except that 1.0 part by mass of red iron oxide (manufactured by LANXESS KK) was used, to obtain a silicone composition (Comparative Example 1) that was liquid at 25°C and a silicone rubber. The viscosity of the silicone composition at 25°C was measured using a B-type rotational viscometer as described in JIS K7117-1:1999. The obtained silicone rubber was also evaluated for thermal conductivity, volume resistivity, rubber properties, and heat resistance according to the evaluation methods described above. The results are shown in Table 2.
[0073] [Comparative Example 2] Example 1 was repeated, except that the cerium oxide used in Example 1 was not used, to obtain a silicone composition (comparison-2) that was liquid at 25°C and a silicone rubber. The viscosity of the silicone composition at 25°C was measured using a B-type rotational viscometer as described in JIS K7117-1:1999. The obtained silicone rubber was also evaluated for thermal conductivity, volume resistivity, rubber properties, and heat resistance according to the evaluation methods described above. The results are shown in Table 2.
[0074] [Comparative Example 3] Example 1 was repeated, except that the iron (III) oxide monohydrate used in Example 1 was not used, to obtain a silicone composition (Comparative Example 3) that was liquid at 25°C and a silicone rubber. The viscosity of the silicone composition at 25°C was measured using a B-type rotational viscometer as described in JIS K7117-1:1999. The obtained silicone rubber was also evaluated for thermal conductivity, volume resistivity, rubber properties, and heat resistance according to the evaluation methods described above. The results are shown in Table 2.
[0075] [Comparative Example 4] A silicone composition (comparison-4) was prepared by repeating Example 1, except that the amount of iron oxide (III) monohydrate used in Example 1 was changed to 12 parts by mass, and the amount of cerium oxide was also changed to 12 parts by mass. However, the resulting composition was in a lump form and could not be made into a liquid paste, so the production of a sheet was abandoned.
[0076] [Comparative Example 5] Instead of the iron(III) oxide monohydrate used in Example 4, hydrate-free iron(III) oxide, Bayferrox 110M (Fe 2 O 3 Example 4 was repeated to obtain a silicone composition (Comparative Example 5) and silicone rubber that were liquid at 25°C, except that 1.0 part by mass of red iron oxide (manufactured by LANXESS AG) was used. The viscosity of the silicone composition at 25°C was measured using a B-type rotational viscometer as described in JIS K7117-1:1999. The thermal conductivity, volume resistivity, rubber properties, and heat resistance of the obtained silicone rubber were evaluated according to the evaluation methods described above. The results are shown in Table 2.
[0077] [Table 1]
[0078] [Table 2]
[0079] [Example 6] An addition reaction type liquid silicone rubber primer No. 31A / B (Shin-Etsu Chemical Co., Ltd.) was applied to the surface of an aluminum shaft with a diameter of 12 mm and a length of 300 mm, and after air drying for 30 minutes, the material was baked in a hot air dryer at 150°C for 15 minutes. This aluminum shaft was fixed in a mold, and the silicone composition of Example 1 (Experimental-1) was poured into the mold at 10 kgf / cm. 2 The silicone rubber roll was filled with water at a pressure of 1000 g / cm2 and heated and cured at 180°C for 30 minutes to obtain a silicone rubber roll (outer diameter 16 mm) with a silicone rubber layer thickness of 2 mm. Next, the silicone rubber roll was covered with a 30 μm thick PFA tube whose inner surface had been treated with primer X-33-173A / B (manufactured by Shin-Etsu Chemical Co., Ltd.) as a release layer for the roll, and then heat-treated for 2 hours in a hot air dryer at 200°C to perform secondary crosslinking of the silicone rubber and adhesion of the primer. The roll obtained above was subjected to heat degradation in a hot air dryer at 230°C for 21 days, and then it was attached to an electrophotographic copier and 1,000 sheets of A4 size copy paper were printed continuously. After that, the surface condition of the roll was checked, but no wrinkles or cracks were found on the roll surface, and all printed images were clear.
[0080] [Comparative Example 6] A roll was produced by repeating the above Example 6, except that the silicone rubber composition of Comparative Example 1 (Comparative-1) was used instead of the silicone rubber composition of Example 1 (Experiment-1). As in Example 6, the roll was subjected to heat degradation for 21 days in a hot air dryer at 230°C. After that, the roll was attached to a thermoelectric copier and 1,000 sheets of A4 size copy paper were printed continuously, but the images became unclear from the 350th sheet onwards. When the surface of the roll was checked, it was confirmed that a scaly pattern had occurred on the surface of the roll and that the rubber part under the PFA had cracked.
[0081] [Example 7] An addition reaction type liquid silicone rubber primer No. 101A / B (manufactured by Shin-Etsu Chemical Co., Ltd.) was applied to the outer peripheral surface of a nickel belt substrate (thickness 30 μm, shape: inner diameter φ30 mm, width 250 mm), and after drying, baking (150 ° C × 15 minutes) was performed. The silicone composition (Experimental-4) of Example 4 was knife-coated thereon, and heated at 200 ° C × 30 minutes to form a silicone layer with a thickness of about 300 μm. A fluorine primer GLP-103SR (manufactured by Daikin Industries, Ltd.) was uniformly applied to the surface of this silicone rubber cured product, dried, and then an aqueous PFA dispersion EJ-CL500 (manufactured by Mitsui Chemours Fluoro Products Co., Ltd.) was applied. The product was heated at 350 ° C for 2 hours to form a 30 μm PFA release layer, and a fluorine resin-coated silicone rubber fixing belt was produced. The fixing belt obtained above was mounted on an electrophotographic copier and 1,000 sheets of A4 size copy paper were continuously printed. After printing 1,000 sheets continuously, the surface condition of the belt was checked, but no wrinkles or cracks were found on the roll surface, and all printed images were clear, confirming that the silicone composition (Example 4) was a material capable of withstanding the PFA film forming conditions of 350°C / 2 hours.
[0082] [Comparative Example 7] A fixing belt was produced by repeating Example 7, except that the silicone composition (Experimental-4) in Example 7 was replaced with the silicone composition (Comparative-5) of Comparative Example 5. As in Example 7, when the belt was attached to an electronic copier and A4 size copy paper was continuously fed through, the images became unclear from the 50th sheet onwards. When printing was stopped and the belt surface was checked, it was confirmed that a wavy pattern had occurred on the surface parallel to the belt axial direction, and that the rubber part under the PFA had cracked.
[0083] As described above, the silicone rubber of the present invention has excellent heat resistance that enables it to retain rubber elasticity even at high temperatures of 230°C or higher, particularly 350°C, and is excellent as a highly thermally conductive silicone rubber for fixing rolls and fixing belts. [Industrial Applicability]
[0084] The silicone rubber obtained by curing the addition-curable liquid silicone composition of the present invention exhibits excellent high-temperature resistance, and can provide a fixing roll or fixing belt that has excellent flexibility and retention over time, and is therefore suitable for use as a member for an image-forming apparatus.
Claims
1. (A) an organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in each molecule and having an average degree of polymerization of less than 1,000: 100 parts by mass, (B) an organohydrogenpolysiloxane having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the ratio of the number of silicon-bonded hydrogen atoms in component (B) to the number of silicon-bonded alkenyl groups in component (A) is 0.3 to 3; (C) a thermally conductive inorganic filler having an average particle size of 1 to 50 μm: 40 to 800 parts by mass, (D) a hydrosilylation reaction catalyst: a catalytic amount, (E) yellow iron oxide: 0.1 to 10 parts by mass, and (F) At least one selected from cerium oxide and cerium hydroxide: 0.1 to 10 parts by mass An addition-curable silicone composition which is liquid at 25°C and contains
2. 2. The addition-curable silicone composition according to claim 1, wherein the thermally conductive inorganic filler (C) is at least one selected from the group consisting of crystalline silica, alumina, metallic silicon, and zinc oxide.
3. 3. The addition-curable silicone composition according to claim 1, which has a viscosity at 25° C. of 1 to 2,000 Pa·s.
4. The addition-curable silicone composition according to any one of claims 1 to 3, which is for use in an image-forming device.
5. A cured silicone rubber product obtained by curing the addition-curable silicone composition according to any one of claims 1 to 4.
6. The silicone rubber cured product according to claim 5, which has a thermal conductivity of 0.4 W / mK or greater.
7. 7. A fixation roll for an image-forming apparatus, comprising: a roll shaft; at least one layer made of the cured silicone rubber according to claim 5 or 6 in contact with an outer circumferential surface of the roll shaft; and a fluororesin layer in contact with one surface of the layer made of the cured silicone rubber.
8. 7. A fixing belt for an image-forming apparatus, comprising: a cylindrical belt; at least one layer made of the cured silicone rubber according to claim 5 or 6 in contact with an outer peripheral surface of the cylindrical belt; and a fluororesin layer in contact with one surface of the layer made of the cured silicone rubber.
Citation Information
Patent Citations
Curable organopolysiloxane composition
JP1995292256A
Addition curing type heat conductive liquid silicone rubber composition
JP2004331962A
Thermosetting silicone rubber composition
JP2014031408A
Heat resistant silicone rubber composition
JP2016518461A
Fluorosilicone elastomer containing iron sulfide
JP2017537213A